Polıtıcal Dıscourse and Cognıtıve Lınguıstıcs - Nigar Babayeva (Balai Publikasi Indonesia, 2024)
One of the fundamental problems of culture is the management of discourse. An individual can sometimes become an object of manipulation by the person controlling the discourse. During the proper discourse, it is possible to control and guide both people with mental disorders and those in custody. In modern scientific literature, the term discourse replaces the terms